Penggunaan Dana Desa Pada Masa Pandemi Covid-19: Studi Desa Kendit Kecamatan Kendit Kabupaten Situbondo - Radhiatul Nurul Jannah; Alwan Sri Kustono; Wahyu Agus Winarno (Jurnal Akuntansi Terapan dan Bisnis, 2022)
This study aims to analyze and determine the planning, implementation and administration of the use of This study aims to analyze and determine the planning, implementation and administration of the use of village funds for the 2020 fiscal year in the context of handling Covid-19 in Kendit Village, Situbondo Regency. This was in accordance with the condition of the village government, at that time experiencing policy confusion. Due to various regulations that change so that it has an impact on the delay in the preparation and changes of the village RKP, preparation of the RAB and APBDes. The type of research used is descriptive qualitative with a case study approach. The research data were secondary and primary data which were further analyzed through triangulation techniques. The results of this study are the process of reallocating the Kendit Village Fund for the 2020 fiscal year carried out in accordance with applicable rules and regulations. The village government does not experience policy confusion regarding changing regulations so that the process runs well. There is a separate policy benchmark carried out by the Kendit Village government in the planning and implementation of the BLT-DD and PKTD programs.